Interleukin-4 in the Generation of the AERD Phenotype: Implications for Molecular Mechanisms Driving Therapeutic Benefit of Aspirin Desensitization - Steinke, John W. (Hindawi Publishing Corporation, 2012)
Aspirin-exacerbated respiratory disease (AERD) is explained in part by over-expression of 5-lipoxygenase, leukotriene C4 synthase (LTC(4)S) and the cysteinyl leukotriene (CysLT) receptors (CysLT1 and 2), resulting in constitutive over-production of CysLTs and the hyperresponsiveness to CysLTs that occurs with aspirin ingestion. Increased levels of IL-4 have been found in the sinus mucosa and nasal polyps of AERD subjects. Previous studies demonstrated that IL-4 is primarily responsible for the upregulation of LTC4S by mast cells and the upregulation of CysLT1 and 2 receptors on many immune cell types. Prostaglandin E(2) (PGE(2)) acts to prevent CysLT secretion by inhibiting mast cell and eosinophil activation. PGE(2) concentrations are reduced in AERD reflecting diminished expression of cyclooxygenase (COX)-2. IL-4 can inhibit basal and stimulated expression of COX-2 and microsomal PGE synthase 1 leading to decreased capacity for PGE(2) secretion. Thus, IL-4 plays an important pathogenic role in generating the phenotype of AERD. This review will examine the evidence supporting this hypothesis and describe a model of how aspirin desensitization provides therapeutic benefit for AERD patients.